2021
DOI: 10.1515/jafio-2020-0036
|View full text |Cite
|
Sign up to set email alerts
|

Japanese Consumers’ Willingness to Pay for Environmentally Friendly Farming Produce Based on Consumer Trustfulness

Abstract: In the past decade, the market share of environmentally friendly farming (EFF) produce in Japan has witnessed relatively rapid growth. However, consumer awareness and purchasing experience of this agricultural produce are still lagging. To study how awareness of EFF produce influences consumer psychology and purchase decisions, we use ordered logistic regression and choice experiments to analyze 600 survey responses collected through online questionnaires. The results show that information from friends and fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
0
1
0
Order By: Relevance
“…For product attributes, in addition to the main variables such as price and appearance, we also set cultivation method and donation amount. Previous studies have shown that cultivation methods, including organic cultivation, influence consumers’ WTP [ 23 , 24 , 25 ]. In the case of apples, special cultivation was adopted as an alternative cultivation method to organic cultivation because fully organic cultivation is technically difficult and organically grown apples are not available in general supermarkets.…”
Section: Methodsmentioning
confidence: 99%
“…For product attributes, in addition to the main variables such as price and appearance, we also set cultivation method and donation amount. Previous studies have shown that cultivation methods, including organic cultivation, influence consumers’ WTP [ 23 , 24 , 25 ]. In the case of apples, special cultivation was adopted as an alternative cultivation method to organic cultivation because fully organic cultivation is technically difficult and organically grown apples are not available in general supermarkets.…”
Section: Methodsmentioning
confidence: 99%
“…Nakagawa [33] showed that direct selling helped enhance the consumer perception of organic rice. Researchers have also designed choice experiments to measure consumers' willingness to pay after providing them with information about the environmental significance of EFF produce in groups [35,36].…”
Section: Trustfulness and Informationmentioning
confidence: 99%
“…This way, the model can be more effective in verifying consumer preferences in actual consumption behavior. Following Yang et al's [36] formula, the utility function of the clogit regression is: For example, after reading the definition of organic and specially cultivated (green food in China) produce, each respondent participated in the choice experiments. Each of the questions included three options: two options containing EFF attributes with price and a "No choice" option.…”
Section: Theorymentioning
confidence: 99%
See 2 more Smart Citations